Endoscopic sinus surgery anatomy, three - dimensional reconstruction and surgical technique - Wormald, P. J. (Thieme, 2013)
This updated and expanded third edition of Endoscopic Sinus Surgery provides detailed, step-by-step instructions on how to perform state-of-the-art surgical techniques on the paranasal sinuses and skull base. It extensively describes the anatomy of all regions within the sinuses and adjacent intracranial cavities and includes unique, practical guidance on using CT scans to reconstruct 3D images of surgical anatomy.